KREATIVITAS GURU PENDIDIKAN AGAMA ISLAM MENGGUNAKAN APLIKASI WORDWALL DALAM MENINGKATKAN AKTIVITAS BELAJAR SISWA DI KELAS VIII A SMPN 2 SALATIGA KECAMATAN SALATIGA TAHUN PELAJARAN 2024–2025. - Muspira; Arnadi; Nurlisa (Lunggi Journal, 2026)
This research began with the discovery of facts in the field which showed that students often lack focus, get sleepy easily, and quickly get bored when learning only uses the lecture method, so that the learning process becomes less effective. To address this, Islamic Education teachers applied digital-based innovation through the wordwall application to enhance students’ attention and learning activity. This study aims to analyze teachers’ creativity in designing, implementing, and evaluating learning using wordwall in Class VIII A of SMPN 2 Salatiga. This research employed a qualitative descriptive approach with data collected through observation, interviews, and documentation. The results show that teachers successfully created interactive wordwall-based materials, implemented engaging learning through quizzes and educational games, and conducted effective digital evaluations. This innovation has been proven to increase students' enthusiasm, motivation, and learning activities in the learning process. Keywords: Creativity, Islamic Education Teacher, Wordwall, Learning Activity